A DNA‐Threaded ZIF‐8 Membrane with High Proton Conductivity and Low Methanol Permeability. Issue 2 (28th November 2017) - Guo, Yi; Jiang, Zhongqing; Ying, Wen; Chen, Liping; Liu, Yazhi; Wang, Xiaobin; Jiang, Zhong‐Jie; Chen, Banglin; Peng, Xinsheng
Abstract: Natural biomolecules have potential as proton‐conducting materials, in which the hydrogen‐bond networks can facilitate proton transportation. Herein, a biomolecule/metal–organic framework (MOF) approach to develop hybrid proton‐conductive membranes is reported. Single‐strand DNA molecules are introduced into DNA@ZIF‐8 membranes through a solid‐confined conversion process. The DNA‐threaded ZIF‐8 membrane exhibits high proton conductivity of 3.40 × 10 −4 S cm −1 at 25 °C and the highest one ever reported of 0.17 S cm −1 at 75 °C, under 97% relatively humidity, attributed to the formed hydrogen‐bond networks between the DNA molecules and the water molecules inside the cavities of the ZIF‐8, but very low methanol permeability of 1.25 × 10 −8 cm 2 s −1 due to the small pore entrance of the DNA@ZIF‐8 membranes. The selectivity of the DNA@ZIF‐8 membrane is thus significantly higher than that of developed proton‐exchange membranes for fuel cells. After assembling the DNA@ZIF‐8 hybrid membrane into direct methanol fuel cells, it exhibits a power density of 9.87 mW cm −2 . This is the first MOF‐based proton‐conductivity membrane used for direct methanol fuel cells, providing bright promise for such hybrid membranes in this application. Abstract : A DNA‐threaded DNA@ZIF‐8 membrane demonstrates ultrahigh proton conductivity and low methanol permeability, holding great potential for application in direct methanol fuel cells.